Productive Zakat Model for Livestock-Based Economic Empowerment: A Fiqh al-Iqtișād Examination of BAZNAS Livestock Centers - Djaenab; Muhammad Alqadri Burga; Rozita Uji Mohammed; Bolu Hasan Basri (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Although productive zakat has been acknowledged as an instrument for mustahik empowerment, there is still no comprehensive, empirically grounded conceptual model for implementing livestock-based productive zakat, including its multidimensional impact assessment—particularly regarding the transformation of mustahik toward sustainable economic self-reliance. This study aims to analyze the BAZNAS Livestock Center program in Barru Regency, focusing on its implementation mechanism, its contribution to poverty alleviation, and the supporting and inhibiting factors that influence its effectiveness. This qualitative research employs a case study approach, with purposively selected informants comprising mustahik beneficiaries and BAZNAS administrators. Data were collected through observation, interviews, and documentation, and analyzed using descriptive techniques. The findings indicate that the BAZNAS Livestock Center program effectively promotes mustahik economic empowerment through livestock asset provision, capacity-building training, and continuous mentoring. The program has improved beneficiaries' incomes, financial literacy, and business independence, though several challenges remain, including livestock risks and limited managerial capacity among the mustahik. This study implies the strategic importance of livestock-based productive zakat as a sharia-compliant social investment instrument rather than merely short-term consumptive assistance. However, this study does not measure long-term impact due to its limited scope and non-longitudinal design; future studies employing mixed-method approaches are recommended. Meskipun zakat produktif telah diakui sebagai instrumen pemberdayaan mustahik, belum tersedia model konseptual berbasis bukti empiris yang komprehensif mengenai implementasi zakat produktif berbasis peternakan beserta pengukuran dampaknya secara multidimensional, khususnya terkait transformasi mustahik menuju kemandirian ekonomi berkelanjutan. Penelitian ini bertujuan untuk menganalisis program Balai Ternak BAZNAS di Kabupaten Barru yang difokuskan pada: mekanisme pelaksanaan program, kontribusi program terhadap pengentasan kemiskinan, dan faktor pendukung dan penghambat keberhasilan program. Penelitian kualitatif ini menggunakan pendekatan studi kasus dengan informan purposive yang terdiri atas mustahik dan pengurus BAZNAS. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, lalu dianalisis menggunakan teknik analisis deskriptif. Hasil penelitian menunjukkan bahwa program Balai Ternak BAZNAS efektif mendorong pemberdayaan ekonomi mustahik melalui pemberian aset ternak, pelatihan, dan pendampingan usaha. Program ini meningkatkan pendapatan, literasi keuangan, dan kemandirian usaha, meskipun masih menghadapi tantangan seperti risiko ternak dan kapasitas manajerial mustahik. Penelitian ini berimplikasi pada pentingnya pengembangan zakat produktif berbasis peternakan sebagai instrumen investasi sosial berbasis syariah, bukan sekadar bantuan konsumtif. Namun, penelitian ini belum mengukur dampak jangka panjang karena keterbatasan cakupan dan desain non-longitudinal, sehingga diperlukan studi lanjutan berbasis mixed methods.